Disintegration and compact measures. - Pachl, Jan K. (MATHEMATICA SCANDINAVICA, 1978)
A probability space is compact in the sense of Marczewski if and only if it admits countably additive disintegrations. It follows that the restriction of a compact measure to a sub-$σ$-algebra is compact.